Physicochemical Factors That Favor Conjugation of an Antibiotic Resistant Plasmid in Non-growing Bacterial Cultures in the Absence and Presence of Antibiotics - Headd, Brendan; Bradford, Scott A. (Frontiers in Microbiology, 2018)
Horizontal gene transfer of antibiotic resistance genes has received increased scrutiny from the scientific community in recent years owing to the public health threat associated with antibiotic resistant bacteria. Most studies have examined horizontal gene transfer in growing cultures. We examined conjugation in growing and non-growing cultures of E. coli using a conjugative multi antibiotic and metal resistant plasmid to determine physiochemical parameters that favor horizontal gene transfer. The conjugation frequency in growing and non-growing cultures was generally greater under shaken than non-shaken conditions, presumably due to increased frequency of cell collisions. Non-growing cultures in 9.1mM NaCl had a similar conjugation frequency to that of growing cultures in Luria-Bertaini broth, whereas those in 1 mM or 90.1 mM NaCl were much lower. This salinity effect on conjugation was attributed to differences in cell-cell interactions and conformational changes in cell surface macromolecules. In the presence of antibiotics, the conjugation frequencies of growing cultures did not increase, but in non-growing cultures of 9.1mM NaCl supplemented with Cefotaxime the conjugation frequency was as much as nine times greater than that of growing cultures. The mechanism responsible for the increased conjugation in non-growing bacteria was attributed to the likely lack of penicillin-binding protein 3 (the target of Cefotaxime), in non-growing cells that enabled Cefotaxime to interact with the plasmid and induce conjugation. Our results suggests that more attention may be owed to horizontal gene transfer in non-growing bacteria as most bacteria in the environment are likely not growing and the proposed mechanism for increased conjugation may not be unique to the bacteria/plasmid system we studied.